The brain microvascular endothelium supports T cell proliferation and has potential for alloantigen presentation. - Julie Wheway (Public Library of Science (PLoS), 2013)
Endothelial cells (EC) form the inner lining of blood vessels and are positioned between circulating lymphocytes and tissues. Hypotheses have formed that EC may act as antigen presenting cells based on the intimate interactions with T cells, which are seen in diseases like multiple sclerosis, cerebral malaria (CM) and viral neuropathologies. Here, we investigated how human brain microvascular EC (HBEC) interact with and support the proliferation of T cells. We found HBEC to express MHC II, CD40 and ICOSL, key molecules for antigen presentation and co-stimulation and to take up fluorescently labeled antigens via macropinocytosis. In co-cultures, we showed that HBEC support and promote the proliferation of CD4(+) and CD8(+) T cells, which both are key in CM pathogenesis, particularly following T cell receptor activation and co-stimulation. Our findings provide novel evidence that HBEC can trigger T cell activation, thereby providing a novel mechanism for neuroimmunological complications of infectious diseases.